APPLICATION OF GLASS-REINFORCED PLASTICS IN AUTO-TRACTOR CONSTRUCTIONS - S. I. Kochetov; T. V. Kipen; S. A. Susha; I. V. Gaysionok (Наука и техника)
The period of high technology development sees large-scale works concerning replacement of conventional materials applied in engineering, in other words metals are replaced by progressive polymer and composite materials, various plastics.Composite materials have found their new application with every passing day in aircraft industry, shipbuilding, electrical engineering, radio engineering, automobile and tractor industry and in other industries displacing conventional ones.Glass-reinforced plastic is considered as one of sufficiently available and widely applicable composite materials because products made of this material are characterized by high physical and mechanical strength indices that surpass steel in performance. This material is not subjected to corrosion and it is resistant to chemically hostile media and environment. These factors determine glass-reinforced plastic longevity. Appearance of a final product plays rather significant role in selection of the required material. Glass-reinforced plastic products can have various shapes preserving their rigidity, strength and small weight.The paper contains a comparative analysis of glass-reinforced plastic properties and it reveals physical and mechanical characteristics of products made of glass-reinforced plastic. The paper also describes peculiar features of glass-reinforced plastic products and their advantages.